Automated Pneumatic System for Car Brake Pedal Test - Ali Rospawan; Joni Welman Simatupang (Jurnal IPTEK, 2021)
In the automotive industry especially in the car production company, after filling the brake fluid oil, the brake fluid should be distributed from the brake fluid oil reservoir tank to all the braking system components. Unfortunately, the oil is not well distributed even an air trapped inside. To prevent the new car brake problem, to replace the human pressing the brake pedal manually, to reduce the manpower effort, and to detect the problem as soon as possible after filling the brake fluid oil this automated pneumatic system for car brake pedal test device is created. This research was done by designing, simulating, create the actual device that is ready to use and implemented in the industry. The result is this system is working well after being successfully implemented. There are several achievements during its operation, especially manpower effort reduction. More safety for the manpower compared to pressing the pedal manually. Safety from electric shock because the system is designed using a full pneumatic system without electricity. Poka-yoke for brake oil leakage, for faster analysis and part replacement, and in the end, it also impacts on the increasing profitability.